Narrating Pedagogical Identity: Mathematics Lecturer Generation Z in the Digital Teaching Era - Nourma Pramestie Wulandari; Isfina Adiyah; Subanji Subanji; Swasono Rahardjo (FKIP Universitas Mataram, 2026)
This study explores the pedagogical identity becoming of Generation Z mathematics lecturers within digital learning contexts. Using a qualitative narrative inquiry design, the study involved two Gen Z mathematics lecturers from Indonesian universities. Data were collected through in-depth interviews and analyzed through narrative storytelling and interpretive thematic analysis. The findings reveal that pedagogical identity develops through a dynamic, non-linear process of becoming shaped by reflection, adaptation, and the negotiation of pedagogical experiences. Technology functions not merely as an instructional tool but as a pedagogical space that shapes teaching practices, relational interactions, and professional meaning-making. The lecturers continuously negotiate closeness, authority, and emotional relationships within digitally mediated classrooms. The study proposes a conceptual model that shows how pedagogical identity emerges from the interconnected experiences of personal history, pedagogical practice, socio-emotional relations, and digital pedagogical spaces.